Auteurs, acteurs, spectateurs - Bernard, Tristan, 1866-1947 (Salt Lake City, UT : Project Gutenberg, 2024)
"Auteurs, acteurs, spectateurs" by Tristan Bernard is a dramatic work written in the early 20th century. The book explores the behind-the-scenes experiences and anxieties of playwrights as they prepare for the premiere of their works. The narrative is likely centered around the thoughts and feelings of a dramatic author, capturing the interplay between the creators, performers, and the audience during the theatrical process. The opening of this piece introduces the reader to the emotional landscape of a playwright on the day of the general rehearsal. The main character observes the hustle and bustle of the theater, feeling both excited and anxious as the moment of performance approaches. Through introspective commentary, he reflects on the challenges of understanding and appeasing the audience a dynamic that often leaves authors feeling at the mercy of their spectators' whims. This exploration sets the stage for a deeper discussion on the nature of theater, the intricacies of performance, and the unpredictable relationship between authors and their audiences. (This is an automatically generated summary.)
Release date is 2024-01-22
Véronique Le Bris, Laurent Vogel and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive/Canadian Libraries)
Keywords: Theater -- France